PENGARUH KEBIJAKAN HUTANG, PROFITABILITAS, LIKUIDITAS DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BEI TAHUN 2017-2021 - Dyah Amalia; Dewi Ayu Wulandari (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to determine the effect of debt policy, profitability, liquidity, and managerial ownership on dividend policy in manufacturing companies listed in Indonesia Stock Exchange in 2017-2021. The sample used for this research is 57 manufacturing companies period 2017-2021. The sampling technique used is purposive sampling, by using multiple linear regression. The results of the study prove that debt policy has a negative and significant effect on dividend policy. Profitability has a positive and significant effect on dividend policy. Liquidity has no effect on dividend policy. Managerial ownership has no effect on dividend policy.